Maternal intake of vitamin E and birth defects, national birth defects prevention study, 1997 to 2005. Issue 9 (17th April 2014) - Gilboa, Suzanne M.; Lee, Kyung A.; Cogswell, Mary E.; Traven, Flavia K.; Botto, Lorenzo D.; Riehle‐Colarusso, Tiffany; Correa, Adolfo; Boyle, Coleen A.; the National Birth Defects Prevention Study
<x xml:space="preserve">Abstract</x> BACKGROUND In a recent study, high maternal periconceptional intake of vitamin E was found to be associated with risk of congenital heart defects (CHDs). To explore this association further, we investigated the association between total daily vitamin E intake and selected birth defects. METHODS: We analyzed data from 4525 controls and 8665 cases from the 1997 to 2005 National Birth Defects Prevention Study. We categorized estimated periconceptional energy‐adjusted total daily vitamin E intake from diet and supplements into quartiles (referent, lowest quartile). Associations between quartiles of energy‐adjusted vitamin E intake and selected birth defects were adjusted for demographic, lifestyle, and nutritional factors. RESULTS: We observed a statistically significant association with the third quartile of vitamin E intake (odds ratio [OR], 1.17; 95% confidence interval [CI], 1.01–1.35) and all CHDs combined. Among CHD sub‐types, we observed associations with left ventricular outflow tract obstruction defects, and its sub‐type, coarctation of the aorta and the third quartile of vitamin E intake. Among defects other than CHDs, we observed associations between anorectal atresia and the third quartile of vitamin E intake (OR, 1.66; 95% CI, 1.01–2.72) and hypospadias and the fourth quartile of vitamin E intake (OR, 1.42; 95% CI, 1.09–1.87). CONCLUSION: Selected quartiles of energy‐adjusted estimated total daily vitamin E intake were associated with selected birth defects. However, because these few associations did not exhibit exposure‐response patterns consistent with increasing risk associated with increasing intake of vitamin E, further studies are warranted to corroborate our findings. Birth Defects Research (Part A), 100:647–657, 2014. © 2014 Wiley Periodicals, Inc.